MON-670 An Overlooked Cause of Diabetic Pain - Arzeno, Luis Enrique (J Endocr Soc, 2020)
Persistent hyperglycemia has been associated with vascular damage in patients with uncontrolled diabetes. Special emphasis has been placed on the heart, kidneys, eyes, and brain since those major organs are vital. However, little has been studied in terms of the vascular supply to the muscle and how it could be affected by high blood glucose. Here we present a 26-year-old female with a history of uncontrolled Type 1 Diabetes Mellitus treated with insulin pump who presented with muscle aches on her right lower extremity. During the evaluation at the Emergency Department (ED), the patient was noted to have diabetes ketoacidosis, intravenous fluids and insulin drip were started. As part of the workup for the muscle aches multiple blood studies were ordered including Creatinine Phosphokinase (CPK) 26 IU/L (25 - 185 IU/L), Erythrocyte Sedimentation Rate (ESR) 102 (0 - 20), C-Reactive Protein (CRP) 3.4 mg/dL (<=0.80 mg/dL), Aldolase 7.5 U/L (<=8.1 U/L), White Blood Cell (WBC) was 13.1 B/L (4.0 - 11.0 B/L). At this point, a muscle biopsy was considered given the lack of evidence to support a definite diagnosis. Before proceeding with the biopsy, a Magnetic Resonance Imaging (MRI) of the low extremities was done, showing diffuse intramuscular edema, predominantly in the right vastus intermedius, with additional patchy intramuscular edema in the right vastus lateralis, vastus medialis, and biceps femoris, as well as the left gluteus maximus, vastus lateralis which were compatible with myositis. Also, discrete areas of myonecrosis in the right vastus intermedialis (1.7 x 1.1 x 3.6 cm), left vastus lateralis (1.7 x 0.8 x 6 cm) and left gluteus maximus (2.8 x 3 cm x 6 cm). Given her previous history of uncontrolled diabetes, the clinical presentation with low CPK levels, lack of data to support another diagnosis, and MRI findings the possibility of diabetes myonecrosis was raised. The patient was managed with conservative therapy: intravenous fluids, pain control and aspirin with improvement in myalgias and muscle strength. Diabetic myonecrosis is a rare condition that appears to be related to vasculopathic changes on uncontrolled diabetics. The lack of specific diagnostic tools and the nonspecific symptoms could make this condition to be overlooked easily; leading to unnecessary studies like muscle biopsy with consequences from complications and increased health care expenditure. A high index of suspicion is essential for timely treatment, which is limited to rest, optimal glycemic control, pain control and patients who are candidates low-dose aspirin. This condition resolves spontaneously over a few weeks to months in most patients and acknowledging this condition could provide timely relief and reassurance.